Pengaruh Pemberian Jus Jambu Biji Merah Terhadap Kadar Hemoglobin Pada Penderita Anemia Remaja Putri di SMK Bunga Persada Cianjur Tahun 2022 - Wulandari Alami; Indri Sarwili; Irma Herliana (Jurnal Anestesi, 2023)
Young women are prone to anemia due to lack of nutrient intake. Anemia is one of the most common health problems in the world today, especially in young women. The impact of anemia can cause weakness, lethargy, and the face becomes pale. So it needs to be handled, one of which is by means of non pharmacological prevention efforts, namely giving red guava juice. The purpose of this study was to determine whether or not there was an effect of giving red guava juice on hemoglobin levels in young women at SMK Bunga Persada Cianjur. This research method uses a quasy experimental research design with a one group pre test – post test design with a purposive sampling model. The result of the study on 17 young female respondents found that the average Hb before being given red juice was 11,5 gr/dl. The average after being given red guava juice is 13,0 gr/dl. So it can be concluded that there is an effect of giving red guava juice with an increase in Hb in anemia sufferers of young women based on the results of data processing using the paired t – test with the results obtained that there is an effect with a value (p value 0,000) (<0,005).